Cicatrices postqueiloplastia: eficacia del láser CO2 fraccionado y la luz pulsada intensa (IPL). Revisión narrativa - Méndez Gaitán, María Paula; Uribe Rodríguez, Mauricio Alfonso; Cianci Uron, Fernando Alberto; Murcia Espino, Sebastián; Vera Rodríguez, Juan Felipe (Revista Ciencias Básicas en Salud, 2025)
Introduction: Post-cheiloplasty scars pose a clinical challenge due to their aesthetic, functional, and psychosocial impact. Fractional CO2 laser and intense pulsed light (IPL) have been used to optimise scar quality, but the evidence remains heterogeneous and there is no consensus on the most effective modality. Methods: A narrative review of the literature was conducted in PubMed and Embase (2015–2025), including clinical trials, systematic reviews, and observational studies. Key clinical outcomes analysed were thickness, texture, pliability, pigmentation, and vascularity. Results: Fractional CO2 laser showed consistent benefits in reducing scar thickness and improving texture and pliability, with greater efficacy when applied in the early phases of healing. IPL was particularly useful for pigmentary and vascular alterations, with a favourable safety profile. Studies evaluating the combination of CO2 and IPL, such as those by Peng and Komisarek, suggest a possible synergistic effect, although methodological limitations persist. Heterogeneity of protocols, small sample sizes, and the limited number of direct head-to-head comparisons restrict the generalisability of the findings.Conclusions: Fractional CO2 laser has the strongest evidence for improving structural parameters of post-cheiloplasty scars, whereas IPL provides complementary benefits for pigmentation and vascularity. Combining both therapies may be a promising strategy, but well-designed, multicentre, controlled trials with standardised protocols and direct comparisons are needed, ideally incorporating quality-of-life outcomes.